Challenges in Educational Management for Implementing Digitalization in Schools - Natalia Togatorop; Citra Chantyka Muslimah; Tari Lasmi Virginia Sihotang; Gaby Sarah Giovani Sigalingging (PT. Global Research Collaboration, 2025)
Digital transformation has brought significant changes to the world of education, requiring educational management to adapt and innovate in managing schools. This article examines the main challenges faced by educational management in implementing school digitalization through a literature review of current scientific sources, both nationally and internationally. The results of the study indicate that the main challenges include technological infrastructure gaps, limited digital competence of teachers, high implementation costs, a lack of digital learning materials, and issues of data security and ethics. The discussion is conducted in-depth to explain the root causes, impacts, and potential solutions to these challenges. This article emphasizes the importance of stakeholder collaboration, continuous teacher training, and the development of adaptive and responsive policies to technological advancements. Thus, the digitalization of education is expected to run optimally and improve the quality of learning in the digital era.